2019
DOI: 10.3390/nu11122939
|View full text |Cite
|
Sign up to set email alerts
|

Oral Administration of Okara Soybean By-Product Attenuates Cognitive Impairment in a Mouse Model of Accelerated Aging

Abstract: The microbiota–gut–brain axis has attracted increasing attention in the last decade. Here, we investigated whether okara, a soybean by-product rich in dietary fiber, can attenuate cognitive impairment in senescence-accelerated mouse prone 8 (SAMP8) mice by altering gut microbial composition. Mice were fed either a standard diet, or a diet containing okara (7.5% or 15%, w/w) for 26 weeks. In the memory test, the 7.5% okara-fed mice showed a longer step-through latency and the 15% okara-fed mice had a short esca… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
13
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 18 publications
(13 citation statements)
references
References 37 publications
0
13
0
Order By: Relevance
“…On the other hand, Wu et al [ 164 ] confirmed the antioxidant activity of black soybean peptide in aging mice caused by d -galactose. In contrast, the study by Corpuz et al [ 161 ] on the oral administration of okara soybean by-products recorded the attenuation of cognitive impairment in a mouse model of accelerated aging. Lastly, Jin and Pyo [ 162 ] also confirmed the effect of monascus-fermented soybean extracts on antioxidant and skin aging-related enzyme inhibitory activities.…”
Section: Anti-aging Effects Of Vegetablesmentioning
confidence: 88%
“…On the other hand, Wu et al [ 164 ] confirmed the antioxidant activity of black soybean peptide in aging mice caused by d -galactose. In contrast, the study by Corpuz et al [ 161 ] on the oral administration of okara soybean by-products recorded the attenuation of cognitive impairment in a mouse model of accelerated aging. Lastly, Jin and Pyo [ 162 ] also confirmed the effect of monascus-fermented soybean extracts on antioxidant and skin aging-related enzyme inhibitory activities.…”
Section: Anti-aging Effects Of Vegetablesmentioning
confidence: 88%
“…A chronic inflammatory state is one of the characteristics of aging and one of the risk factors for the high incidence of various age-dependent chronic diseases [ 8 , 31 , 40 ]. High levels of proinflammatory cytokines were associated with the loss of muscle mass and poor physical function in older adults.…”
Section: Discussionmentioning
confidence: 99%
“…SAMP8 (Senescence Accelerated Prone Mouse 8) mice, developed from the AKR/J strain, are a rapid aging mouse model, which have the advantage of having short lifespans and experiencing accelerated aging processes. To compare SAMP8 mice with an accelerating senescence rate, SAMR1 (Senescence Accelerated Resistant Mouse 1) are usually utilized [ 31 , 32 , 33 ]. Compared with SAMR1mice, it has been reported that SAMP8 mice showed decreased muscle strength, muscle fiber size and muscle phosphocreatine level with aging [ 34 ].…”
Section: Introductionmentioning
confidence: 99%
“…3,4 Previous studies have also revealed that adding okara to the daily diet could regulate body characteristics; for example, the high fiber and high protein contents in okara caused short-chain fatty release to promote gut health, which contributed to the reduction of liver lipid accumulation in diet-induced obesity. 5 These contents also increased the NeuN intensity in the hippocampus to accelerate aging, 6 and lowered fasting blood glucose and fructosamine to regulate diabetes. 7 Furthermore, the high fiber content of okara saved the abundant Bifidobacterium, Enterococcus, and C. leptum from the induction of the highfat diet of rats, which were producers of butyrate and provided the protection of intestinal health.…”
Section: Introductionmentioning
confidence: 99%